Induced Chirality in Sulfasalazine by Complexation With Albumins: Theoretical and Experimental Study - Grandini, Giulia Saneti [UNESP]; Ximenes, Valdecir Farias [UNESP]; Morgon, Nelson Henrique; de Souza, Aguinaldo Robinson [UNESP] (Wiley, 2024)
Through molecular recognition, drugs can interact and complex with macromolecules circulating in the body. The serum albumin transport protein, found in several mammals, has several interaction sites where these molecules can be located. The drug sulfasalazine (SSZ) is known in the literature to complex at drug site 1 (DS1) in human serum (HSA) and bovine serum (BSA) proteins. This complexation can be studied using various spectroscopic techniques. With the techniques used in this work, absorption in the ultraviolet and visible regions (UV–Vis) and electronic circular dichroism (ECD), a significant difference was observed in the results involving HSA and BSA. The application of theoretical methodologies, such as TD-DFT and molecular docking, suggests that the conformation that SSZ assumes in DS1 of the two proteins is different, which exposes it to different amino acid residues and different hydrophobicities. This difference in conformation may be related to the location of DS1 where the drug interacts or to the possibility of SSZ moving in the BSA site, due to its larger size, and moving less freely in HSA.
Keywords: BSA; HSA; molecular docking; sulfasalazine; TD-DFT; UV-ECD